New records of rare genera of the subfamily Doryctinae (Hymenoptera: Braconidae), with description of five new species from Vietnam - Long, Khuat Dang; Hoa, Dang Thi; Duong, Nguyen Van (Academia Journal of Biology, 2017)
Three small genera of the subfamily Doryctinae are newly recorded for the Braconidae fauna of Vietnam, viz. Euscelinus Westwood, 1882; Leptospathius Szépligeti, 1902 and Sonanus Belokobylskij & Konishi, 2001. Five new species of these genera are described and illustrated, namely Euscelinus vietnamicus Long, sp. n.; Leptospathius langsoni Long, sp. n.; Leptospathius phamvanluci Long, sp. n.; Leptospathius simulatus Long, sp. n. and Sonanus mocchaui Long, sp. n.. The checklist and distribution of the already known species of three genera are provided. Keys to species of the genera are also given. Keywords: Braconidae, Doryctinae, new record, new species, rare genera, Vietnam.Citation: Khuat Dang Long, Dang Thi Hoa, Nguyen Van Duong, 2017. New records of rare genera of the subfamily Doryctinae (Hymenoptera: Braconidae), with description of five new species from Vietnam. Tap chi Sinh hoc, 39(4): 383-397. DOI: 10.15625/0866-7160/v39n4.10897(*): Corresponding author: khuatdanglong@gmail.com